THE INFLUENCE OF STUDY HABITS ON LEARNING MOTIVATION AND ACADEMIC ACHIEVEMENT IN DIGITAL SIMULATION SUBJECT: A QUANTITATIVE STUDY AT A VOCATIONAL HIGH SCHOOL - Yandria Elmasari; Annisaa Fadhila (JoEICT (Jurnal of Education And ICT), 2025)
Study habits represent a critical internal factor that shapes students’ academic trajectories, yet the differential effects of study habits on motivational outcomes versus cognitive achievement remain insufficiently understood in the context of vocational secondary education. This study investigates the influence of study habits on two distinct learning outcomes—learning motivation (Y₁) and academic achievement (Y₂)—among Grade X students enrolled in the Digital Simulation and Communication (SIMDIG) subject at SMKN 2 Tulungagung, Indonesia. A quantitative correlational design was employed, with data collected from 76 students selected via purposive sampling (15% of the total population of 505 students) across three classes. Data were obtained through a closed Likert-scale questionnaire (1–4) validated via SPSS (19 valid items for study habits; 22 for learning motivation) and supplemented with mid-term examination scores as the academic achievement indicator. Simple linear regression and t-test analyses were applied after confirming the assumptions of normality, linearity, homogeneity, and homoscedasticity. Results revealed that study habits significantly predicted learning motivation (sig. = 0.000, R = 0.682, R² = 0.465), accounting for 46.5% of the variance, whereas no significant relationship was observed between study habits and academic achievement (sig. = 0.283, R = 0.125, R² = 0.016). These findings suggest that while consistent study habits substantially enhance student motivation in vocational ICT settings, academic achievement is governed by a broader constellation of internal and external factors. Practical implications for vocational educators and future research directions involving multivariate and digital-mediated learning environments are discusse.